1995
DOI: 10.1111/j.1423-0410.1995.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Transfusion Hyperhaemolysis in a Patient with Sickle Cell Disease: Use of Steroids and Intravenous Immunoglobulin to Prevent Further Red Cell Destruction

Abstract: Delayed haemolytic transfusion reactions (DHTRs) are seen more frequently in patients with sickle cell disease (SCD) than in other groups of patients, and are characterised by a positive direct antiglobulin test and the appearance of previously undetected red blood cell (RBC) alloantibodies in the patient's serum. Recently a syndrome of post-transfusion hyperhaemolysis has been described in children with SCD, characterised by destruction of both autologous and transfused RBCs with negative serological findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 13 publications
2
59
0
1
Order By: Relevance
“…While IVIG was beneficial 3 cases, 20,21 in the fourth case there was a temporal relationship between IVIG administration and the occurrence of a sickle cell crisis. 22 Our data raise the possibility that IVIG may be beneficial in preventing or treating sickle cell vaso-occlusion.…”
Section: Resultsmentioning
confidence: 95%
“…While IVIG was beneficial 3 cases, 20,21 in the fourth case there was a temporal relationship between IVIG administration and the occurrence of a sickle cell crisis. 22 Our data raise the possibility that IVIG may be beneficial in preventing or treating sickle cell vaso-occlusion.…”
Section: Resultsmentioning
confidence: 95%
“…Previously described patients usually received corticosteroid therapy, 6,7,14 IVIg, 8 or both. 5,9,21 The protocol currently used at our institution involves IVIg infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid and/or intravenous immunoglobulin (IVIg) therapy has been reported to ensure recovery from DHTR. [5][6][7][8][9]13,14 More recently, two studies reported the use of rituximab for preventing DHTR. 13,15 The pathophysiology of this syndrome remains unclear, especially when there is no detectable antibody.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid drop in Hb level may be contributed by hyperhaemolysis syndrome. It is regarded as a separate clinical manifestation that can only follow a DHTR [6]. The exact mechanism of hyperhaemolysis syndrome is not well understood.…”
Section: Discussionmentioning
confidence: 99%